Gender equity in disability sport: A rapid scoping review of literature - Culver, Diane; Shaikh, Majidullah; Alexander, Danielle; Duarte, Tiago; Sljuka, Vincenzo; Parrott, Laura; Wrona, Darien; Fournier, Karine (Université d'Ottawa | University of Ottawa, 2020)
This literature review is a foundational document for the E-Alliance Gender+ Equity in Sport in Canada Research Hub. Lead by Dr. Diane Culver [and Shaikh, M., Alexander, D., Sjluka, V., Duarte, T., Wrona, D., Parrott, L., Fournier, K.], the research team searched six databases (Medline, Embase, SPORTDiscus, Physical Education Index, PsycINFO, Web of Science) for research related to understanding gender equity in disability sport. From an initial yield of 1542 records, two phases of screening were undertaken, resulting in 128 records selected for extraction. Data were extracted from the records in categories related to context, sample, methodologies, and results information; data were additionally reviewed and further narrowed to 45 records ready for synthesis. Descriptive statistics were generated from these data categories, and qualitative descriptive analyses were used to group data inductively into themes that can help address the research question. Key findings included: (a) ableist and masculinity notions are intertwined into disability sport, and shape the experiences of disabled athletes, (b) disabled athletes are often challenged with how to construct their identities, and (c) contemporary media perpetuates the notions of masculinity and ability in their representations of female disabled athletes. In terms of gaps: (a) limited research in understanding gender equity in disability sport in Canada, and (b) limited data participation rates in disability sport by gender across levels of involvement (e.g., organizational, coaching, athletic, etc.) and across context (e.g., elite, Paralympic, recreational, school, etc.). Based on the results from our review, future gender+ equity in sport in Canada research should focus on: (a) more research in gender equity in the Canadian disability context, (b) exploring recreational and schools as places of opportunity to promote gender participation, and (c) collaborative action research approaches to tackle research questions most relevant to disabled people and supporting their empowerment.